It Takes a Village A Collaborative Assault on the Struggling Reader Dilemma - Rattigan-Rohr, Jean.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
It Takes a Village: A Collaborative Assault on the Struggling Reader Dilemma has a wellspring of incredibly useful information for teacher educators, pre-service and in-service teachers alike. It shows quite clearly that preparing effective reading teachers while addressing issues related to (a) readers who struggle (b) parental inclusion, and (c) the inclusion of the wider community can be done quite successfully. This book puts readers in touch with compelling insights into the importance of parental inclusion in the educational efforts of their children. Additionally, it provides a "counter narrative" to the belief by many that parents and in particular, racial and ethnic minority parents, do not participate with their children in academic endeavors. The text also focuses on key aspects of teacher preparation especially as it relates to reading instruction. The author provides a wonderful variety of step-by-step approaches for how to seamlessly transition teacher reading instruction from the lecture hall to the "village" practice sites. The book is well written with the authentic voices of parents, students and pre-service teachers. This book is an excellent contribution to the literature concerning issues related to struggling readers, parental inclusion and community involvement. - Samuel Miller, Associate Dean, University of North Carolina Greensboro.
Keywords: Education; Education; Education (general).